The Predicaments of Muslims in the Philippines: An Exposition of Said Nursi’s Hypothesis vis-à-vis Hizmet Movement Approach - Cayamodin, Jamel Rombo; Durakoglu, Abdulhamit (Studia Islamika, 2021)
The complexities of interdependent predicaments experienced by Muslims propel their pessimism on the prospect of reform in the Philippines. This pessimism has made the apathy of Muslims towards the corrupt system in the country. Consequently, this condition drives the weakening of altruism and increases apathetic social identifiers. These predicaments continue until the current day due to the lack of inclusive and effective remedies for improving the rudiments of people’s living in contemporary society. By using analysis of documents and in-depth interviews, the writers examine the root causes of Muslim-Filipinos’ interdependent predicaments according to Said Nursi’s hypothesis vis-à-vis Hizmet Movement approach. The study finds that Said Nursi’s “triumvirate quandaries hypothesis” resembles, to a greater extent, the interdependent predicaments of Muslims in the Philippines. Thus, inclusive remedies concurrent to the approaches of the Hizmet Movement that are known to have effectively addressed the triumvirate quandaries need to be contextualized in the Muslim-Filipino society within the context of the Philippines secular state.